2010
DOI: 10.1186/1475-2859-9-81
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage, self-cycling process for the production of bacteriophages

Abstract: BackgroundA two-stage, self-cycling process for the production of bacteriophages was developed. The first stage, containing only the uninfected host bacterium, was operated under self-cycling fermentation (SCF) conditions. This automated method, using the derivative of the carbon dioxide evolution rate (CER) as the control parameter, led to the synchronization of the host bacterium. The second stage, containing both the host and the phage, was operated using self-cycling infection (SCI) with CER and CER-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 214 publications
1
29
0
Order By: Relevance
“…The research presented here has shown that by narrowing the conditions used and focussing on those that positively influence phage infection, the titer achieved is reliable and validated at small scale and in a scale‐up system which focuses on larger volumes, automation, and controllable parameters, that is, pH and DO 2 . Previous studies have shown a greater variance in titer achieved compared to our work as no optimization of the bioprocess was performed (Bourdin et al, ; Sauvageau & Cooper, ). Improving the phage bioprocess in shake flasks allows more rapid experiments to be completed which can then be moved into a stirred tank system.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The research presented here has shown that by narrowing the conditions used and focussing on those that positively influence phage infection, the titer achieved is reliable and validated at small scale and in a scale‐up system which focuses on larger volumes, automation, and controllable parameters, that is, pH and DO 2 . Previous studies have shown a greater variance in titer achieved compared to our work as no optimization of the bioprocess was performed (Bourdin et al, ; Sauvageau & Cooper, ). Improving the phage bioprocess in shake flasks allows more rapid experiments to be completed which can then be moved into a stirred tank system.…”
Section: Resultsmentioning
confidence: 61%
“…Previous studies have shown a greater variance in titer achieved compared to our work as no optimization of the bioprocess was performed (Bourdin et al, 2014;Sauvageau & Cooper, 2010).…”
Section: Scale-upmentioning
confidence: 70%
“…Phages are typically produced in batch fermenters e.g., shaken flasks, and more recently in disposable wave bags that are used for tissue cell culture; there are no real issues with regard to residence times and complex control strategies [ 23 , 24 ]. The downsides for industrial scale batch fermentation include higher capital costs, large process footprints, labour-intensive operation, that the proportion of downtime compared with production time can be high, a lack of process control, and variability of product quality [ 24 ]. The continuous upstream production of phages using chemostat systems has heretofore received little attention in the published literature, which instead has focused on using such systems for studying coevolution processes [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Decoupling the bacterial host propagation from phage production removes the selection pressure for bacteria mutation and should allow stable long-term steady-state operation of the process [ 28 ]. Semi-continuous production approaches using such a strategy include a two-stage self-cycling process for the production of phages [ 24 , 29 , 30 ]. Synchronous host populations at high cell concentrations are produced in the first reactor operated in batch mode.…”
Section: Introductionmentioning
confidence: 99%
“…The authors hypothesized that the larger cellular protein synthesizing system of older cells, not simply a larger cell volume, is the more important determinant of infection outcome. In addition, a study on the use of synchronized cultures of Escherichia coli in bacteriophage production found evidence that phage productivity was considerably larger for a synchronized culture than an asynchronous one, even at slower growth rates (Sauvageau & Cooper, ).…”
Section: Introductionmentioning
confidence: 99%